Prototipe Sistem Pengkondisian Sirkulasi Udara Pada Lapangan Futsal Mini Dengan Metode Fuzzy Logic - Uyun Amalia, Rahma; Wijayanto, Ardik; Rusminto, Tjatur Widodo (ALINIER: Journal of Artificial Intelligence & Applications, 2023)
The implementation of the New Normal is carried out in all aspects of community activities, to keep the body healthy it is necessary to do regular exercise. Futsal is one of the sports that is currently trending and is carried out in a sports hall, so that the futsal field building also needs to reach a new normal. In order to maintain the function of the futsal field as a healthy place, a system is needed to maintain air circulation in the futsal field. Air circulation in the futsal field needs to be controlled in order to maintain the air temperature at a certain temperature and minimize the impact of the spread of the covid19 virus by limiting the number of people in the futsal field building. The system built to realize this is by implementing air circulation control using fuzzy logic with temperature parameters and counting the number of people on the futsal field. The sensors used in this study are DHT22 which functions to measure temperature and IR (InfraRed) sensors which function as a counter for the number of people. The ESP32 module is used for sending data collected from sensor readings via the wifi network to android via the blynk application. The results of the research that has been done is that the Fuzzy control can work well, because it can maintain a temperature of no more than 31.97oC, whereas if you don't use the temperature control it will read 32.84oC and will continue to increase